2014
DOI: 10.4102/sajip.v40i1.1193
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of the industrial-organisational psychologist as counsellor

Abstract: Orientation: Industrial-organisational (I-O) psychologists are often confronted with counselling interventions in the workplace and thus it is vital that they are effectively prepared for their role as workplace counsellors.Research purpose: The aim of this study was to review the role of I-O psychologists as counsellors and to ascertain whether these practitioners are effectively prepared for this purpose.Motivation for the study: I-O psychologists are mainly concerned with the deep-rooted problems individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Some participants also used the terms counselling, coaching and check-ins in a synonymous manner. Barkhuizen et al ( 2014 ) correspondingly reported participants’ view that coaching is closely related to counselling. From an international perspective, IOPs are viewed as particularly qualified to provide coaching, and that many IOPs formally engage in coaching activities (American Psychology Association, 2013 ; Society for Industrial and Organizational Psychology, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some participants also used the terms counselling, coaching and check-ins in a synonymous manner. Barkhuizen et al ( 2014 ) correspondingly reported participants’ view that coaching is closely related to counselling. From an international perspective, IOPs are viewed as particularly qualified to provide coaching, and that many IOPs formally engage in coaching activities (American Psychology Association, 2013 ; Society for Industrial and Organizational Psychology, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Pienaar and Roodt (2001) suggest that IOPs should emerge from their academic training fully equipped with counselling competencies (e.g. expressive and empathic communication and listening skills) that will help them operate ethically and effectively in the workplace (see also Barkhuizen et al, 2014;Ivey, Ivey, & Zalaquett, 2013;Johnson & Kaslow, 2014;McLeod, 2020) The second preparedness subordinate theme was related to experience -participants indicated that, because they did not typically deliver mental health counselling services, they had little experience in doing so when called upon during the COVID-19 pandemic. It appeared that, under usual circumstances and even during the pandemic when there was a clear increase in the need for counselling, the IOP response was to outsource this function to clinical psychologists and other professionals.…”
Section: Responsiveness Of Workplace Industrialorganisational Psychologists To Employees' Counselling Needs During the Pandemicmentioning
confidence: 99%
See 2 more Smart Citations
“…Industrial and organisational psychology is the scientific study of individual, group and organisational behaviour in the workplace and is aimed at optimising performance throughout (Cilliers & Flotman, 2016). The IO psychologist is additionally tasked to help his or her clients manage talent resources (Ganaie & Haque, 2017;Theron, 2009;Wilcox, 2016), ensuring a work environment that is focused on the well-being and individuality of the employee (Lawler, 2011;Van Vuuren, 2010) and on challenges that the employee faces outside of the work environment (Barkhuizen, Jorgensen, & Brink, 2014;Landy & Conte, 2016).…”
Section: Introductionmentioning
confidence: 99%